(In)Expediency of Conducting English Language Placement Tests in Ukrainian Higher Education Institutions - Babushko, Svitlana; Solovei, Liudmyla (Educological discourse, 2025)
The issue of conducting an English placement test in domestic higher education institutions is the subject of active discussions. Its main purpose is to determine the level of English proficiency and form academic groups of students with approximately the same level for further study of English for Specific Purposes in a higher education institution. However, in practice, there arise a number of challenges and problems that need to be resolved. Therefore, the purpose of the article is to comprehensively cover this problem in order to clarify the feasibility or inexpediency of placement test implementation. The authors analyzed the degree of scientific study of the problem in the foreign and domestic scientific environment. It was found that the problem is in the circle of scientific interests of foreign researchers, who focus on the methods of developing such tests, their objectivity and reliability, and structure. Unfortunately, the issue of studying the feasibility of conducting such a diagnostic test in the Ukrainian context remains insufficiently examined. To objectively highlight the problem, the authors used SWOT analysis, which allowed them to identify the strengths and weaknesses of conducting a placement test, its opportunities and threats. The results of the analysis showed that conducting an English placement test to determine the level of English language competence of first-year students has a number of advantages and disadvantages for both students and teachers. Given the complexity of the issue and the limitations of scientific research in Ukraine, further comprehensive study of the feasibility of conducting English placement tests is necessary. It is important to involve stakeholders in the discussion, in particular students and teachers of higher education institutions, in order to form a substantiated decision on the (in)expediency of English level tests in higher education institutions.